2023
DOI: 10.1002/ptr.8016
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde inhibits cytokine storms induced by the ORF3a protein of SARS‐CoV‐2 via ROS‐elimination in activated T cells

Jing Ma,
Xu Chen,
Rui Xue
et al.

Abstract: Cytokine storms are the cause of complications in patients with severe COVID‐19, and it becomes the target of therapy. Several natural compounds were selected to screen the inhibitory effect on T‐cell proliferation by Fluorescence‐Activated Cell Sorting (FACS) and cytokine production by enzyme‐linked immunosorbent assay (ELISA). Open reading frame 3a (ORF3a) of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) stimulates the specific T‐cell activation model in vivo and in vitro. The coculture system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Additionally, FDA-approved drugs like doxycycline, metformin, and ibrutinib also exhibit inhibitory effects on ORF3a-mediated inflammasome activation [51]. Cinnamaldehyde, a natural compound acting as an NLRP3 inflammasome inhibitor, has demonstrated efficacy in vitro and in vivo by reducing inflammatory cytokine and ROS production in activated T-cells [123]. Other drugs targeting the NLRP3 pathway have been investigated in clinical trials or considered for repurposing to manage cytokine storms in COVID-19.…”
Section: Testing Well-established Druggable Cellular Targets Of Key O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, FDA-approved drugs like doxycycline, metformin, and ibrutinib also exhibit inhibitory effects on ORF3a-mediated inflammasome activation [51]. Cinnamaldehyde, a natural compound acting as an NLRP3 inflammasome inhibitor, has demonstrated efficacy in vitro and in vivo by reducing inflammatory cytokine and ROS production in activated T-cells [123]. Other drugs targeting the NLRP3 pathway have been investigated in clinical trials or considered for repurposing to manage cytokine storms in COVID-19.…”
Section: Testing Well-established Druggable Cellular Targets Of Key O...mentioning
confidence: 99%
“…During acute infection, anti-NLRP3 inflammasome drugs could mitigate cytokine storms, especially important in older individuals [51,123]. A direct ORF3a inhibitor capable of addressing acute and chronic effects would be ideal, although no such inhibitor is known currently.…”
Section: Challenges and Future Prospectivesmentioning
confidence: 99%
“…CA scavenges free radicals and enhances the activity of endogenous antioxidant enzymes [ 112 ], for example, Ismail found that CA enhances cardiac antioxidant activity through the reduction of malondialdehyde (MDA) levels and the increase in activities of glutathione S-transferase (GST), superoxide dismutase (SOD), catalase, reduced glutathione (GSH), and glutathione peroxidase (Gpx) [ 113 ], which play crucial roles in cellular defense against oxidative damage [ 114 ]. Recently, Ma et al performed fluorescence-activated cell sorting (FACS) and cytokine production through enzyme-linked immunosorbent assay (ELISA) and found that CA inhibited the cytokine storm induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) open reading frame 3a (ORF3a) protein by eliminating ROS in activated T cells [ 115 ]. The primary antioxidant mechanism of TCA involves the inhibition of ROS production and the activation of crucial oxidative stress defense systems, including Nrf2 and the thioredoxin signaling pathways [ 116 ].…”
Section: The Role Of Cinnamaldehyde In Cancer Preventionmentioning
confidence: 99%